From Macroeconomy to the Firm Level: Revisiting the Resource Curse Hypothesis in Vietnamese Listed Companies - Minh Ngoc Trinh (Jurnal Ilmiah METHONOMI, 2026)
This study examines whether the resource curse hypothesis, originally formulated at the country level, also manifests among individual firms in a resource-dependent economy. The analysis employs a panel dataset of 11,937 firm-year observations from 1,406 non-financial companies listed on the Vietnamese stock market over the period 2015 to 2023. A time invariant resource sector indicator is constructed using industry classification codes and verified against corporate names. Profitability, measured by return on assets, and asset growth serve as the dependent variables, with firm size, leverage, tangibility, and year fixed effects included as controls. To ensure robust inference, all models are re-estimated using firm, clustered standard errors and a random effects estimator. When the resource indicator is defined broadly to encompass oil and gas, coal, and mineral extraction, it exhibits no statistically significant association with profitability. The coefficient on return on assets is 0.00491 and remains insignificant under both clustered standard errors and random effects. In sharp contrast, restricting the indicator to the oil and gas subsector reveals a pronounced negative effect. Firms in this subsector exhibit a return on assets approximately 3.13 percentage points lower than their counterparts, with a coefficient of -0.03133 that is significant at the one percent level and remains robust to firm-level clustering. Moreover, the same subsector demonstrates significantly lower asset growth, with a coefficient of -0.08512 that is consistent across all three estimators. Collectively, these findings extend the resource curse debate to the firm level and underscore the substantive empirical implications of industry heterogeneity within the broadly defined resource sector, suggesting that the curse, if present, is not a general feature of resource-intensive industries but rather a subsector-specific phenomenon concentrated in oil and gas.